2019
DOI: 10.1080/13674676.2019.1592136
|View full text |Cite
|
Sign up to set email alerts
|

Exploring two approaches to an existential function of religiosity in mental health

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Individuals who engage in deep reflection are likely to exhibit greater acceptance and flexibility in coping with the loss. By confronting existential issues, individuals can develop a potential capacity for personal growth and increased awareness of the struggles associated with existence 23 . This heightened awareness can lead to an increase in distress tolerance, ultimately resulting in a reduction in the severity of mourning experienced by the bereaved family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who engage in deep reflection are likely to exhibit greater acceptance and flexibility in coping with the loss. By confronting existential issues, individuals can develop a potential capacity for personal growth and increased awareness of the struggles associated with existence 23 . This heightened awareness can lead to an increase in distress tolerance, ultimately resulting in a reduction in the severity of mourning experienced by the bereaved family members.…”
Section: Discussionmentioning
confidence: 99%
“…By confronting existential issues, individuals can develop a potential capacity for personal growth and increased awareness of the struggles associated with existence. 23 This heightened awareness can lead to an increase in distress tolerance, ultimately resulting in a reduction in the severity of mourning experienced by the bereaved family members. Some studies have suggested that mediating factors, such as the meaning of life, coping strategies, and religiosity, may play a role in the relationship between existential thinking and grief‐related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has confirmed that religion can play a positive role in human life, leading to better mental health and higher subjective wellbeing through finding meaning in life (Stewart et al 2017;Giannone et al 2019;Wnuk and Marcinkowski 2014;Krok 2015) and positive emotions such as hope (Wnuk and Marcinkowski 2014;Nell and Rothmann 2018), optimism (Cheadle et al 2018;Aglozo et al 2021), gratitude (Jang et al 2018;Kane et al 2021), and forgiveness (Jang et al 2018;Sharma and Singh 2019;Kane et al 2021) through social support (Nooney and Woodrum 2002;Holt et al 2005), as well as effective coping (Holt et al 2005).…”
Section: Introductionmentioning
confidence: 99%